MINERALIZATION OF THE BUSANG PROSPECT, EAST KALIMANTAN - Harry Utoyo (Puslitbang tekMIRA, 2014)
Busang prospect occurs in the Kalimantan Volcanic belt of East Kutai Regency, East Kalimantan. The prospect occupied the undulated morphology known as Bukit Busang. It is approximately 150 km southwest of the Kelian mine. Geologically, the Busang prospect is hosted within the volcanic rocks (tuff, breccia, dacite and adesite). The volcanic sequences are intruded by the Oligo-Miocene Atan Diorite. The hydrothermal alteration consists of silicification and argillic assemblages. Silicification is the presence of quartz and opaline silica while the argillic alteration is characterized by the presence of illite-kaolin clay. Mineralogy of the deposit comprises of gold, minor chalcopyrite, lead, sphalerite, pyrite and marcasite. Style of mineralization is quartz veins and dissemination within the host rocks. Analytical results from quartz samples show that the content of gold ranges from 0.016-66,06 ppm, Cu : 29-1810 ppm, Pb : 925-117675 ppm and Zn : 197-24908 ppm. The fluid inclusion measurement from two quartz veins indicate that the homogenization temperature ranges from 317.3-323.0ºC. The fluid salinity is very low, 0.5 wt % NaCl. On the basis of mineralogy, hydrothermal alteration, quartz textures and homogeniza- tion temperature, the Busang prospect is categorized as a low sulfidation epithermal type. The genetic model of the Busang prospect is possibly due to the intrusion of the Oligo-Miocene Atan Diorite.